2007
DOI: 10.1002/micr.20380
|View full text |Cite
|
Sign up to set email alerts
|

Lower leg replantation—Decision‐making, treatment, and long‐term results

Abstract: Our results as well as those of other large series show that lower leg replantation is still worthwhile in a well selected patient group, contrary to what is believed by an increasing number of orthopaedic and trauma surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
(67 reference statements)
0
26
0
Order By: Relevance
“…Only if the patient can walk independently with the transplanted legs is the procedure warranted. Lower limb replantation has typically been contraindicated due to reported poor results . Recently encouraging results of leg replantation have been published .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only if the patient can walk independently with the transplanted legs is the procedure warranted. Lower limb replantation has typically been contraindicated due to reported poor results . Recently encouraging results of leg replantation have been published .…”
Section: Discussionmentioning
confidence: 99%
“…Lower extremity transplantation has typically been contraindicated, assuming the theoretical risks would outweigh the benefits. Classically, even lower limb replantation after traumatic amputation has been discouraged , although good results have been reported in below‐knee (BK) replantations recently .…”
Section: The Recipientmentioning
confidence: 99%
“…In the majority of the publications the authors do not distinguish between reported cases of distal and proximal lower limb amputations/replantations. They usually evaluate these cases as a homogenous group, [11] albeit physiological factors influencing the outcome of replantations are more advantageous in case of lower leg replantations [12] than those of replantations performed above the knee and in the mid-third of the thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for amputation-like injuries of the lower limb are either aimed at the provision of a stump that is suitable for early prostheses fitting or reconstruction. 33 The advantage with primary amputation is a rapid rehabilitation process and a quick return to a functional life. Delaying an inevitable amputation leads to greater: length of hospitalization, physical and psychological deconditioning, disability, financial burden, false hope and risk of death.…”
Section: Discussionmentioning
confidence: 99%